Identification of a Potyvirus Infecting Groundnut, Arachis hypogeae L.,in Malaysia - Abdul Samad, Norani (1984)
A virus disease showing leaf mottling in groundnuts, Arachis hypogeae cv. V 13, was observed in experimental plots at the Universiti Pertanian Malaysia, Serdang, West Malaysia, in 1982. The virus is sap-transmissible and can also be transmitted by the aphid, Aphis craccivora Koch, in a non-persistent manner. The host range is narrow. It produced chlorotic local lesions in Chenopodium amaranticolar Coste & Reyn and systemic chlorotic lesions in Vigna sinensis Sav. Electron microscopic examination of virus infected groundnut leaves revealed'the presence of long flexuous particles about 800 nm in length and pinwheel inclusions in tissue sections; therefore, the virus belongs to the potyvirus group.